AGRESIVITAS ANAK KORBAN EKSPLOITASI DI PASAR KODIM KECAMATAN SENAPELAN PEKANBARU - Laili, Anggi; Umari, Tri; Putra, Roby Maiva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study determines to find out the aggressive behavior carried out (perpetrators) and to know the aggressive behavior experienced by (victims) of child exploitation victims as well as factors that encourage children victims of exploitation to behave aggressively. This type of descriptive research with qualitative approach is research to describe a variable based on phenomenological problems. Data analysis techniques are data reduction, data feed, and data verification or conclusion. Data collection techniques used are interviews and observations directly to children victims of exploitation in the market kodim district senapelan pekanbaru age range of 5-12 years consists of 4 subjects. The results of this study are 3 children victims of exploitation (RD, NF, and RV) committing (perpetrators) aggressiveness such as stealing, squabbling, taunting, and revenge. 3 child victims of exploitation (RJ, RD, and NF) experienced (victims) aggressiveness such as being pinched, abused, mocked, threatened, told friends, beaten, and angry friends. Factors that encourage aggressive behavior are internal conditions, external (social) factors, and environmental stressors.Key Words: Aggressiveness, Child Exploitation Victims, Descriptive Research QualitativeApproach